Efektifitas Media Promosi Dalam Meningkatkan Kunjungan Wisata Alam - Zulin Zulin (JURNAL SOSIAL Jurnal Penelitian Ilmu-Ilmu Sosial, 2021)
Abstract— Research with the title Effectiveness of Media Promotion in Increasing Natural Tourism Visits in Nongko Ijo Village of Kare, Kec. Kare, Kab. Madiun. This research discusses the extent to which the level of community readiness in developing Nongko Ijo Tourism Village. The data in this study were obtained from direct observation through questionnaires and interviews with the people of Kare Village, Kecamagtan Kare, Madiun Regency. As a tour manager as well as to several tourists who are in the Nongko Ijo Tourism Village. The results of this study indicate that the readiness of the community in developing the Nongko Ijo Tourism Village is very high seen from several aspects, namely, attractions, accessibility, and amenities. The evaluation of this research can be useful for future development. The community participates in developing their village into one of the villages. Keywords—: Nongko Ijo; Nature Tourism; Forest.